Faktor Keterlibatan Jepang dalam Perang Dunia II pada Film Rengou Kantai Shirei Choukan Yamamoto Isoroku - Wedagama, I Dewa Gede Radiantha; Budiana, I Made (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2022)
Japan is one of the countries that was actively involved in World War II. In the war, Japan joined Germany and Italy to fight the US and its allies. However, World War II ended with Japan's defeat in 1945. This study aims to determine the factors of Japan's involvement in World War II in the film Rengou Kantai Shirei Choukan Yamamoto Isoroku by Izuru Narushima. Data was collected using the method of observation and documentation. The collected data was analyzed using descriptive analysis method and the results are presented using informal methods. The theory used in this research is the New Historicism theory by Greenblatt (1980). The results of the analysis show that there are three factors behind Japan's involvement in World War II. The three factors are 1) the belief that war can end the economic crisis; 2) Japan's dream of liberating Asia; and 3) the memory of Japan's victories in wars in the past.